In vivo direct relation of tau pathology with neuroinflammation in early Alzheimer’s disease - Terada, Tatsuhiro; Yokokura, Masamichi; Obi, Tomokazu; Bunai, Tomoyasu; Yoshikawa, Etsuji; Ando, Ichiro; Shimada, Hitoshi; Suhara, Tetsuya; Higuchi, Makoto; Ouchi, Yasuomi (Journal of neurology, 2019)
Objective Neuronal damage and neuroinflammation are important events occurring in the brain of Alzheimer’s disease (AD). The purpose of this study was to clarify in vivo mutual relationships among abnormal tau deposition, neuroinflammation and cognitive impairment in patients with early AD using positron emission tomography (PET) with [ 11 C]PBB3 and [ 11 C]DPA713. Methods Twenty patients with early AD and 20 age-matched normal control (NC) subjects underwent a series of PET measurements with [ 11 C]PBB3 for tau aggregation and [ 11 C]DPA713 for microglial activation (neuroinflammation). Inter- and intrasubject comparisons were performed regarding the levels of [ 11 C]PBB3 binding potential (BP ND ) and [ 11 C]DPA713 BP ND in the light of cognitive functions using statistical parametric mapping (SPM) and regions of interest (ROIs) method. Results The [ 11 C]PBB3 BP ND was greater in the temporo-parietal regions of AD patents than NC subjects, and a similar increasing pattern of [ 11 C]DPA713 BP ND was observed in the same patients. Correlation analyses within the AD group showed a positive direct correlation between [ 11 C]PBB3 BP ND and [ 11 C]DPA713 BP ND in the parahippocampus. Pass analysis revealed that cognitive impairment was more likely linked to the level of the parahippocampal [ 11 C]PBB3 BP ND than that of [ 11 C]DPA713 BP ND . Conclusions The pattern of abnormal tau deposition was very similar to that of neuroinflammation in patients with early-stage AD. Specifically, the direct positive correlation of tau pathology with neuroinflammation in the parahippocampus suggests that neuronal damage in this region is closely associated with microglial activation. Consistently, tau aggregation in this region matters more than neuroinflammation regarding the cognitive deterioration in AD.